Atypical Presentation of COVID-19 Incidentally Detected at 18F-FDG PET/CT in an Asymptomatic Oncological Patient. (August 2020) - Mattoli, Maria Vittoria; Taralli, Silvia; Pennese, Elsa; D'Angelo, Carla; Angrilli, Francesco; Villano, Carlo
Abstract : Abstract: The incidence of COVID-19, a severe acute respiratory syndrome caused by SARS-CoV-2, is rapidly growing worldwide. In this pandemic period, the chance of incidental pulmonary findings suggestive of COVID-19 at 18 F-FDG PET/CT in asymptomatic oncological patients is not negligible. To suspect COVID-19 is more demanding whether its presentation is atypical. We describe the incidental PET/CT detection of an 18 F-FDG–avid isolated centrilobular pulmonary consolidation in an asymptomatic lymphoma patient, which later resulted in an unexpected and atypical COVID-19 presentation. The nuclear medicine physicians should be prepared to suspect COVID-19 even in asymptomatic patients presenting with a "far-from-COVID-19" finding at PET/CT.